Beyond the Marvelous City: narratives and imaginaries about heritage in postcards of Baixada Fluminense - Siqueira, Euler David de; Siqueira, Denise da Costa Oliveira (RITUR - Revista Iberoamericana de Turismo, 2023)
Situated outside the tourist imaginary and also outside the circuits and guidebooks of Rio de Janeiro, Baixada Fluminense is located in the shadow of the significance zone of the state capital. For decades, this region has been represented in the media as an abandoned place, marked by social tragedies, violence, poverty, and lack of leisure and cultural activities, but it hides a vast "cultural and natural" heritage. Part of this heritage can be found represented in postcards. Based on this observation, we asked what representations of Baixada Fluminense can be found in postcards of the region. To what extent do these old conventional media raise aspects that contrast with the narratives of the commercial and conglomerate media? This qualitative research adopts a comprehensive sociology approach in order to investigate the imaginary present in a small representative sample of postcards of the city of Nova Iguaçu. Some preliminary results point to the presence of an artistic and historical heritage capable of allowing a reflection beyond stereotypical aspects.